Mobile Health: general concepts and its potential to be implemented in Cuba - Adrián Trimiño-Alcántara; Joel Antonio Fernández-Moreno; Mireya Martínez-Velázquez; Román Savón-Plutin (Revista Información Científica, 2022)
Introduction: the use of Digital and Communication Technologies are currently part of the daily activities of society. Mobile health (mHealth) is one of the most developed nowadays, on one hand, due to the new normality generated by the COVID-19 pandemic, but also far away, due to the relevant advantages acquired for mobile telephone technologies over other technologies.